Determinants of computer attitudes among undergraduates of Nanyang Technological University - Goh, Kim Chai (2008)
This study sets out to investigate the determinants of computer attitude of undergraduates of Nanyang Technological University (NTU) based on a sample of 488 full-time students. The General Linear Model was employed in the study to analyse the effects of demographic factors and other variables on computer attitudes.